2012
DOI: 10.1111/j.1479-828x.2011.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Serial plotting on customised fundal height charts results in doubling of the antenatal detection of small for gestational age fetuses in nulliparous women

Abstract: Serial plotting of the FH on customised charts supported by a clinical practice guideline resulted in a doubling of the antenatal detection of SGA in nulliparous pregnant women at low risk for SGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 12 publications
3
28
4
1
Order By: Relevance
“…A reduction in perinatal mortality in SGA infants late in pregnancy requires a combination of increased detection and optimal timing of birth. Increased antenatal detection of SGA can be achieved with implementation of customised antenatal growth charts in routine antenatal care 2. The recommendations from this article regarding the optimum timing of delivery (37–38 weeks) are consistent with data from other epidemiological studies which show an increase in SGA perinatal mortality after 37 weeks, with a particular increase after 38 weeks.…”
Section: Commentarysupporting
confidence: 80%
“…A reduction in perinatal mortality in SGA infants late in pregnancy requires a combination of increased detection and optimal timing of birth. Increased antenatal detection of SGA can be achieved with implementation of customised antenatal growth charts in routine antenatal care 2. The recommendations from this article regarding the optimum timing of delivery (37–38 weeks) are consistent with data from other epidemiological studies which show an increase in SGA perinatal mortality after 37 weeks, with a particular increase after 38 weeks.…”
Section: Commentarysupporting
confidence: 80%
“…12 SFH as a predictor of SGA may also be limited by the presence of fibroids, the contribution of amniotic fluid and descent of the presenting part in late pregnancy. Observational studies have reported that the use of customised fundal height charts can approximately double the detection of SGA, 13 although this has not yet been tested in randomised studies.…”
Section: Clinical Detection Of Late-onset Fgrmentioning
confidence: 99%
“…FGR is defined as the inability of a fetus to reach its genetically determined growth potential (Kusinski, Stanley, Dilworth, Hirt, Andersson, Renshall, Baker et al 2012). Characteristics of FGR include reduced birth weight, abnormal placentation, fetal hypoglycaemia, hypoxia and increased fetal cortisol concentrations (Economides, Nicolaides, Campbell 1991 McCowan, Thompson, Taylor, North, Poston, Baker, Myers et al 2013) and 42 % of early neonatal deaths (Roex, Nikpoor, van Eerd, Hodyl, Dekker 2012) in the Western world. The metabolic changes associated with maternal obesity such as insulin resistance, hypertension, elevated triglycerides, increased systemic inflammatory profiles and oxidative stress can lead to placental insufficiency (Hajer, van Haeften, Visseren 2008;Huang, Yu, Keim, Li, Zhang, Zhang 2014) and mitochondrial abnormalities in the placenta (Mele, Muralimanoharan, Maloyan, Myatt 2014).…”
Section: Introductionmentioning
confidence: 99%